Lexical and phraseological differences between second language written and spoken opinion responses - Kim, Minkyung; Crossley, Scott A. (Frontiers in Psychology, 2023)
This study examines differences in lexical and phraseological complexity features between second language (L2) written and spoken opinion responses via classification analysis. The study further examines the characteristics of L2 written and spoken responses that were misclassified in terms of lexical and phraseological differences, L2 learners’ vocabulary knowledge, and raters’ judgments of L2 use. The goal is to more thoroughly explore potential differences in lexical and phraseological production based on modality. The results indicated that L2 written responses tended to elicit greater lexical and phraseological complexity. The results also indicated that crossing the boundaries from L2 spoken to written (i.e., the use of less lexical and phraseological complexity) was related to lower levels of L2 vocabulary knowledge and tended to be penalized by raters in terms of L2 use. In contrast, crossing the boundaries from L2 written output to spoken (i.e., the use of greater lexical and phraseological complexity) was acceptable in terms of L2 use. Overall, this study highlights lexical and phraseological differences and the importance of the use of greater lexical and phraseological complexity in a modality-insensitive manner in L2 opinion-giving responses.